Original paperAutologous intradermal skin tests in women with Hashimoto’s thyroiditis - Sadowska-Przytocka, Anna; Czarnecka-Operacz, Magdalena; Łącka, Katarzyna; Jenerowicz, Dorota (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction : In a large proportion of patients with chronic urticaria, a coexisting autoimmune type of Hashimoto’s thyroiditis is being diagnosed. An intradermal test with autologous serum has been generally considered as a screening procedure indicating the presence of triggering autoimmune inflammatory factors in the sera of patients with urticaria. These factors could be possibly involved in the pathogenesis of the disease. Now, it seems that in order to complete the screening diagnostic procedures of autoimmune component in patients with spontaneous chronic urticaria, intradermal tests with autologous plasma could be also useful. Aim : To assess skin reactivity in patients suffering from the autoimmune type of Hashimoto’s thyroiditis with serum and plasma intradermal tests. Material and methods : Thirty-five female patients with Hashimoto’s thyroiditis aged 23-78 years were recruited for our study. The control group consisted of 20 healthy volunteers with a negative history and no signs or symptoms of any thyroid as well as autoimmune diseases. Intradermal tests with autologous plasma, serum and with 0.9% NaCl (negative control) were performed. Results : Five patients with the autoimmune type of Hashimoto’s thyroiditis presented positive results of the autologous serum test (14.2%) while positive results of the autologous plasma test were obtained in 2 cases (5.7%). It seems to be important that subjects with positive results of intradermal tests have not been treated with L-thyroxine. In the case of healthy volunteers results of our diagnostic procedures were negative. Conclusions : This study suggests that thyroid suppression by L-thyroxine can result in clinical remission of urticaria symptoms.